A snapshot of information-seeking behavior literature in health sciences: a bibliometric approach - Abu Bakar, Ahmad Bakeri; Ibrahim Harande, Yahya (University of Nebraska--Lincoln Libraries, 2010)
This study is a snapshot on the literature of information-seeking behavior in the discipline of health sciences during the years 2000-2007. A total of 801 papers were identified in Medline through the PubMed database. Bibliometric analysis was conducted to explore growth of the literature, authorship patterns, and Bradford distribution of the literature and language of dispersion of the literature. The findings indicate that there is a rapid growth of information-seeking behavior in health sciences from 2004 onward. On the language of dispersion of the literature, English was found to be dominant with score of 56 percent, followed by French with 23 percent. Bradford's distribution was used and found to be applicable to this literature despite the fact that the shape of the graph does not depict the “S” shape. The study was concentrated on two domains, nursing, with 505 papers, and psychoanalysis, with 296. Multi-author papers were scattered in both domains,constituting 66.9 percent.